A aplicação da função linear na comercialização artesanal dos brinquedos de miriti no Ramal Tauerá de Beja no município de Abaetetuba-PA - CARVALHO, Elliene Crisley Pires (2019)
This paper deals with the application of the linear function in the artisanal commercialization of miriti toys in the Tauerá branch of Beja in the municipality of Abaetetuba / PA. In order to investigate the commercialization of miriti toys, a field research is done with the artisan Augusto Costa da Costa, whose activity is to make different designs of the toys, selling them at the branch, at the candle festival in Belém / Pa and to the outside (French Guiana). The field research carried out at the Tauerá branch in Beja corresponds to a semi-structured questionnaire with questions of a qualitative and qualitative nature, seeking to identify the importance of craftsmanship as a source of income for the craftsman, as well as the profits obtained from the sale of miriti toys inland, inland and abroad. For a better understanding of the source of income of the craftsman, he develops, in parallel, a study on linear function, trying to equate the revenues related to costs and sales of toys, in order to show if the marketing corresponds to a satisfactory profit for the researched. In this way, the linear function is relevant to show, at the same time, an effective way for the artisan to make a financial balance on the revenue for the three sales sites. This article concludes that the mathematics related to the study of function can be a strong ally to evaluate profits and losses and, at the same time, to construct a financial balance on a certain activity, that in the present case, the commercialization of miriti toys, whose raw material comes from the very property from which it withdraws to make the toys and sell as family means of support.